Oposisi Makna dalam Bahasa Lio - Suryati, Ni Made (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This study aims to describe and explain: (1) the types of antonyms in the Lio language; (2) the categories of Lio antonyms; and (3) the linguistic units that may express oppositional meanings in Lio. The study is based on semantic theory, particularly the theory of antonymic word-meaning relations. The data were collected through direct observation and interviews, supported by note-taking and audio recording techniques. The results show that: (1) there are five types of antonymic relations in Lio, namely (a) absolute opposition, (b) polar opposition, (c) relational opposition, (d) hierarchical opposition, and (e) compound opposition; (2) the lexical categories that exhibit antonymic relations include (a) nouns, (b) pronouns, (c) numerals, (d) verbs, and (e) adjectives; and (3) antonymic relations occur in several linguistic forms, namely (a) base form versus base form, (b) base form versus prefixed form, (c) prefixed form versus prefixed form, (d) base form versus word group, and (e) word group versus word group.